Cover Picture: Extensive Sodium Metal Plating and Stripping in a Highly Concentrated Inorganic−Organic Ionic Liquid Electrolyte through Surface Pretreatment (ChemElectroChem 5/2017). Issue 5 (28th April 2017) - Basile, Andrew; Makhlooghiazad, Faezeh; Yunis, Ruhamah; MacFarlane, Douglas R.; Forsyth, Maria; Howlett, Patrick C.
Abstract : The Front Cover picture highlights how gaining access to sodium across the globe is relatively simple, owing to the large abundance of element in the Earth's crust. The image is used to show this in comparison to other alkali metals used as battery anodes. More information can be found in the Communication by A. Basile et al. onpage 986 in Issue 5, 2017 (DOI:10.1002/celc.201600784 ).